2021
DOI: 10.5114/kitp.2021.109407
|View full text |Cite
|
Sign up to set email alerts
|

The impact of dual antiplatelet therapy administration on the risk of bleeding complications during coronary artery bypass surgery

Abstract: Introduction: Dual antiplatelet therapy reduces the risk of cardiovascular death, myocardial infarction and recurrence of adverse ischemic events in patients affected by acute coronary syndromes, but in patients urgently needing coronary artery surgery it can increase the risk of severe perioperative bleeding complications. Aim: We evaluated the impact of dual antiplatelet therapy (DAPT) based on acetylsalicylic acid plus clopidogrel or ticagrelor in patients undergoing coronary artery bypass grafting (CABG). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Furthermore, in the last 5 years, the need to urgently perform CABG on patients undergoing single or double anti-aggregating therapy has become increasingly frequent, due to the highrisk coronary anatomy and because in clinical practice many patients have intracoronary stents positioned shortly before carrying out CABG, thus necessarily requiring the dual antiplatelet therapy. Anyway, we observed in a previously published study [28] that bleeding requiring surgical exploration in patients on dual antiplatelet therapy (aspirin plus clopidogrel), i.e., 44% of the sample, although higher (2.4% vs. 1.2%), did not increase the risk of in-hospital mortality.…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, in the last 5 years, the need to urgently perform CABG on patients undergoing single or double anti-aggregating therapy has become increasingly frequent, due to the highrisk coronary anatomy and because in clinical practice many patients have intracoronary stents positioned shortly before carrying out CABG, thus necessarily requiring the dual antiplatelet therapy. Anyway, we observed in a previously published study [28] that bleeding requiring surgical exploration in patients on dual antiplatelet therapy (aspirin plus clopidogrel), i.e., 44% of the sample, although higher (2.4% vs. 1.2%), did not increase the risk of in-hospital mortality.…”
Section: Discussionmentioning
confidence: 63%
“…Of these, 8 compared suspending DAPT (defined as holding P2Y12 inhibition with continuation of acetylsalicylic acid [ASA]) at various preoperative timepoints, which we dichotomized as ≤ 2 days withdrawal or > 2 days withdrawal. Of note, 1 study that grouped 48–72 h was placed in the > 2 days withdrawal group [ 23 ]. A second study had comparison groups of 0–3 days and > 4 days, which were reassigned to ≤ 2 and > 2 withdrawal days, respectively [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were 4 observational CABG studies that reported mortality risk differences across comparison arms (shown in Fig. 5 ) and 1 additional study [ 23 ] that reported mortality as odds ratios. None of these reported significant differences in patient death across DAPT management strategies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation